Kemampuan Membaca Al-Qur'an Anak Usia 8 Tahun Melalui Metode Ummi di Rumah Al Qur'an Baitus Shuffah Bandar Lampung - Aldi Syaiful Huda Aldi; Chairul Anwar; Era Octafiona (WISE Pendidikan Indonesia, 2026)
Qur’anic reading competence is a fundamental component of Islamic education for children, yet variations in children’s ability to recognize hijaiyah letters, articulate Arabic phonemes, apply tajwid rules, and read fluently remain a persistent challenge in nonformal Qur’anic learning contexts. This study aimed to describe the Qur’anic reading ability of eight-year-old children learning through the Ummi Method at Rumah Qur’an Baitus Shuffah, Bandar Lampung, and to identify the supporting and inhibiting factors influencing the learning process. Employing a descriptive qualitative case-study design, the study involved one Qur’an teacher and two eight-year-old students selected through purposive sampling. Data were collected through classroom observation, semi-structured interviews, and documentation, and were analyzed using the stages of data reduction, data display, and conclusion drawing. The findings reveal that the Ummi Method was implemented through direct instruction, teacher modelling, talaqqi, repeated reading practice, corrective feedback, and interactive learning activities adapted to children’s developmental characteristics. The students demonstrated positive Qur’anic reading competence, as indicated by their ability to recognize hijaiyah letters, pronounce most letters according to makharij al-huruf, apply basic tajwid rules, and read Qur’anic texts with adequate fluency. Supporting factors included the teacher’s pedagogical creativity, consistent repetition, direct correction, and a conducive learning environment, whereas limited concentration and difficulty articulating specific Arabic letters, particularly ṭā’ (ط), emerged as learning obstacles. This study implies that structured, repetitive, and teacher-guided Qur’anic instruction through the Ummi Method can strengthen early Qur’anic literacy in nonformal Islamic education, while collaboration among teachers, institutions, and parents is essential to sustain children’s reading development beyond classroom practice.